МOSCOW INSTITUTE OF NATIONAL ECONOMY TO PLEKHANOV RUSSIAN ACADEMY OF ECONOMICS: PLEKHANOVKA IN THE END 1980 – 1990th YEARS - I. M. Kornilova (Plekhanov Russian University of Economics, 2018)
The article is devoted to the history of the Plekhanov Russian University of Economics in the period of perestroika and his transformation from the Moscow Institute of National Economy to the Russian Economic Academy. On the basis of archival materials, the author made an attempt to understand what trends formed the basis for the transformations made in the late 1980s and early 1990s, what goals and objectives the university leadership set for itself, what price and what was achieved despite all Shocks and transformations, through which the Russian state and society had to pass. The article presents an analysis of the tasks set by the leadership of the Moscow institute of national economy in the Comprehensive Program of Social and Economic Development of the Institute for the period up to 2010, adopted in 1987. Despite the fact that its implementation was corrected by historical processes, much of what was planned at the first stage was implemented and formed the basis for the modernization of the university that began then. The scientific value of the article lies in the fact that it is written with the use of previously unexplored archival materials that allow a better understanding of the processes and problems associated with the transition of the university to a self-supporting system and the introduction of profiling. In addition, the article presents the dynamics of the volume of scientific research and its funding in the university in 1987–1991.